The K3N3 Formula in the Implications of Institutional Change Management of PTKIN with a Multi-Aspect Approach - Sari, Elly Kartika; Ridwan, Muhtadi; Esha, Muhammad In'am (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Change management in Islamic higher education institutions presents unique complexities due to the interplay between spiritual values, academic structures, identity formation, and market competitiveness. Despite various transformation efforts, many institutions still lack an integrative framework that links the change process to measurable institutional outcomes. Institutional change in Islamic higher education institutions (PTKIN) is a response to external dynamics such as policies, the labor market, and technological developments. Similarly, internal dynamics are influenced by institutional vision and leadership practices. These dynamics require appropriate formulation to have a valuable impact on the organization. This article examines the implications of change management in Islamic higher education institutions (PTKIN). The purpose of this paper is to explore the implications of institutional change in PTKIN through the case of the transformation that occurred at UIN Sultan Aji Muhammad Idris (UINSI) Samarinda. The research method is a qualitative case study; data were obtained through observation, interviews, documentation, and analysis using NVivo 12 Pro. The results show the implementation of change management systematically it produces structured implications in the form of the K3N3 formula. The K3N3 concept is an abbreviation for 3K (institutional strength, identity strength, market strength) and 3N (competitive value, institutional image value, organizational selling point). Institutional strengthening (structure, accreditation, capacity), identity strengthening (name, philosophy of scientific integration), and market strengthening (graduate utilization) are each manifested as competitive value, institutional image, and organizational selling point. These findings offer a practical conceptual framework for PTKIN leaders who wish to manage institutional change sustainably.